Pendidikan Informal Melaui Spiritualitas Alam dalam Novel Mata dan Rahasia Pulau Gapi Karya Okky Madasari - Muhammad Kriswanto; Muh. Fatoni Rohman (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
Natural spirituality is the harmony of the human soul with nature in order to maintain and preserve the universe. It needs to be nurtured and strengthened in humans so as not to exalt destructive nature so that there is a need for nature-based education through literary forms in every child's growth process. The focus of this study is to describe the picture of natural spirituality and informal education through natural spirituality, which is constructed in the novel